2004
DOI: 10.1111/j.1365-2133.2004.05749.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in acne scarring: a comparison of the responses in lesions from patients prone and not prone to scar

Abstract: The cellular infiltrate was large and active with a greater nonspecific response (few memory T cells) in early lesions of NS patients, which subsided in resolution. In contrast, a predominantly specific immune response was present in S patients, which was initially smaller and ineffective, but was increased and activated in resolving lesions. Such excessive inflammation in healing tissue is conducive to scarring and suggests that the use of topical anti-inflammatory treatments would be appropriate for these pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
119
0
10

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(139 citation statements)
references
References 24 publications
10
119
0
10
Order By: Relevance
“…In the majority of patients, the clinical picture is characterized by the infl ammatory/immunological disease component. In severe cases (conglobate acne), follicular rupture causes foreign body reactions to comedonal components (corneocytes, hairs) ( Figure 1 [ 4 ] . Less severe disease courses, too, may result in scarring.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In the majority of patients, the clinical picture is characterized by the infl ammatory/immunological disease component. In severe cases (conglobate acne), follicular rupture causes foreign body reactions to comedonal components (corneocytes, hairs) ( Figure 1 [ 4 ] . Less severe disease courses, too, may result in scarring.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Scarring acne shows a predominantly CD45RO+memory T cell immune response, which is initially small and ineffective, but later becomes increased and activated in resolving lesions. In contrast with non-scarring acne, the cellular infiltrate is large and active with few memory T cells in early lesion, which subsides in the resolution phase [3].…”
Section: Pathophysiology Of Scar Formationmentioning
confidence: 90%
“…Holland et al observed that in inflammatory lesions from patients who have less scarring, there is a brisk inflammatory cellular infiltrate composed of T-helper lymphocytes, macrophages, and Langerhans cells, with accompanying angiogenesis that quickly resolves compared with patients who are prone to scarring, where the inflammation and angiogenesis start slowly but is maintained over a longer period. It is speculated that the prolonged inflammatory response in patients prone to scarring is a delayed-type hypersensitivity reaction to persistent antigenic stimulus that they were initially unable to eliminate [36]. As there is no tool to predict who will develop this delayed-type reaction, treating early inflammation is the best approach to prevent acne scarring.…”
Section: Inflammatory Responsesmentioning
confidence: 99%